The effect of restricting the perceptual task in temporal organization of crawl swimming: surface characteristics - Brito, C. A. F.; Belvis, W. C.; Oliveira, M. (Biomechanics and Medicine in Swimming XI, 2010)
The objective of this study was to observe how disturbing swimming skill execution can influence the superficial parameters of front crawl. There was mixed random-systematic sampling among 5% of high-ability swimmers from São Caetano do Sul, enrolled with DETUR in 2008 (n=106). Disturbance was carried out by light shone onto the retina, forming a configuration according to the degree of complexity. The subjects swam at a natural rhythm. Data were analyzed using Mauchly`s Test of Sphericity and repeated measures ANOVA (Contrast). Probability was 5% (p<0.05). We observed significant differences (p<0.05) in the variable parameters (time, speed, distance and swimming strategy) of front crawl after perception manipulation, even when maintaining the distance to be executed and a normal swimming rhythm.